Comparison of Complete Distal Release of the Medial Collateral Ligament and Medial Epicondylar Osteotomy during Ligament Balancing in Varus Knee Total Knee Arthroplasty - Sim, Jae Ang (The Korean Orthopaedic Association, 2013)
BACKGROUND: During ligament balancing for severe medial contracture in varus knee total knee arthroplasty (TKA), complete distal release of the medial collateral ligament (MCL) or a medial epicondylar osteotomy can be necessary if a large amount of correction is needed. METHODS: This study retrospectively reviewed 9 cases of complete distal release of the MCL and 11 cases of medial epicondylar osteotomy which were used to correct severe medial contracture. The mean follow-up periods were 46.5 months (range, 36 to 78 months) and 39.8 months (range, 32 to 65 months), respectively. RESULTS: There were no significant differences in the clinical results between the two groups. However, the valgus stress radiograph revealed significant differences in medial instability. In complete distal release of the MCL, some stability was obtained by repair and bracing but the medial instability could not be removed completely. CONCLUSIONS: Medial epicondylar osteotomy for a varus deformity in TKA could provide constant medial stability and be a useful ligament balancing technique.